2006
DOI: 10.1021/bi060754b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ligands on the Mobility of an Active-Site Loop in Tyrosine Hydroxylase as Monitored by Fluorescence Anisotropy

Abstract: Fluorescence anisotropy has been used to monitor the effect of ligands on a mobile loop over the active site of tyrosine hydroxylase. Phe184 in the center of the loop was mutated to tryptophan, and the three native tryptophan residues were mutated to phenylalanine to form an enzyme with a single tryptophan residue in the mobile loop. The addition of 6-methyl-5-deazatetrahydropterin to the enzyme resulted in a significant increase in the fluorescence anisotropy. The addition of phenylalanine did not result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
(71 reference statements)
1
30
0
Order By: Relevance
“…Thus, r ∞ and r 0 − r ∞ are the contributions (i.e., amplitudes) of the slow global rotation and the faster local rotation, respectively, to the anisotropy. The value of θ 2 , which reflects the motion of the entire protein, was fixed at 115 ns based on our earlier study of the fluorescence properties of TyrH (13). When the data for the phosphorylated and unphosphorylated forms of each mutant enzyme were analyzed individually, the resulting values of r 0 and θ 1 were independent of the phosphorylation status for each mutant protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, r ∞ and r 0 − r ∞ are the contributions (i.e., amplitudes) of the slow global rotation and the faster local rotation, respectively, to the anisotropy. The value of θ 2 , which reflects the motion of the entire protein, was fixed at 115 ns based on our earlier study of the fluorescence properties of TyrH (13). When the data for the phosphorylated and unphosphorylated forms of each mutant enzyme were analyzed individually, the resulting values of r 0 and θ 1 were independent of the phosphorylation status for each mutant protein.…”
Section: Resultsmentioning
confidence: 99%
“…To address this limitation, we have used fluorescence spectroscopy to probe changes in the dynamics and solvent accessibility of residues in the regulatory domain upon phosphorylation of Ser40. We have previously shown that mutating all three intrinsic tryptophans in TyrH to phenylalanines has little effect on enzyme activity or substrate binding (13). We describe here the use of this tryptophan-free enzyme to study the effects of phosphorylation on the conformation of the N-terminus of TyrH.…”
mentioning
confidence: 99%
“…While substantial structural changes in response to pterin binding to TyrH have been observed in fluorescence anisotropy studies of a flexible polypeptide loop associated with the metal binding site (45) , X-ray crystallographic studies of TyrH have shown that no structural changes are associated with the binding of 7,8-dihydrobiopterin to the ferric enzyme (7) . Considering these previous findings, it is most likely that the large change in β hf reflects a change in the coordination of NO with respect to bound tyrosine when 6-MPH 4 is bound.…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopic studies of PheH and TyrH show that the ligands to the active site iron in both undergo a change from 6-coordinate to 5-coordinate when both the amino acid substrate and a tetrahydropterin are bound [83, 84]. In addition, the surface loop in TyrH that corresponds to the Tyr138 loop also shows significant motion upon substrate binding [85], although the regulatory mechanism and accompanying structural changes in that enzyme are different from those for PheH [3, 86, 87]. The structural changes detected by HXMS upon binding to rat PheH lacking the regulatory domain are much more localized than is the case for the intact enzyme [71], suggesting that binding to the regulatory site is required for large conformational changes.…”
Section: Structural Basis For Regulation Of Phenylalanine Hydroxylasementioning
confidence: 99%